OPTIMALIZATION OF LOCAL PHYTOBIOTIC AS ANTIBIOTIC REPELACEMENT ON INCREASING PRODUCTIVITY OF NATIVE CHICKEN ON MARGO MULYO VILLAGE: OPTIMALISASI PHYTOBIOTIC LOKAL SEBAGAI PENGGANTI ANTIBIOTIK DALAM PENINGKATAN PRODUKTIVITAS AYAM KAMPUNG DI DESA MARGO MULYO - ETHA 'AZIZAH HASIIB; Rudy Sutrisna; RR RIYANTI; KHAIRA NOVA; FITRIA TSANI FARDA; ALI HUSNI; DONI RAMADHAN; EVA APRILIA (CV. Multi Kreasi Media, 2022)
Margo Mulyo Village is village located in Jati Agung Sub-district with general agricultural potential. One of the potentials is native chicken and biopharmaceutical plants. To develop the productivity of native chicken, biopharmaceutical plants can be used as phytobiotic green additives to replace antibiotics which are now banned. The objectives of this study are: 1. implementing the tridharma; 2. provide information to the farmer of Margo Mulyo Village on the use of phytobiotic green additives in increasing the productivity of native chicken; and 3. increase public awareness of increasing the productivity of native chicken. This community service was carried out in Margo Mulyo Village, Jati Agung District, South Lampung Regency. The target for this activity is farmers in the village. The method to be implemented is counseling by way of lectures and providing examples of simple applications in the provision of phytobiotics to increase the productivity of native chicken. The counseling activity was carried out with zoom meeting on July 21th , 2021, while the field visit was carried out on July 22th , 2021 in Margo Mulyo Village. The results showed that farmers have increased ability in maintenance management, recording management, feeding management, and the provision of biopharmaceutical plants for native chicken.